2001
DOI: 10.1063/1.1330252
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation study of plasma-enhanced chemical vapor deposited and rf sputtered hydrogenated amorphous silicon carbide films

Abstract: Thermal dissociation process of hydrogen atoms in plasma-enhanced chemical vapor deposited silicon nitride films J. Appl. Phys. 84, 5243 (1998); 10.1063/1.368813Infrared and x-ray photoelectron spectroscopy studies of as-prepared and furnace-annealed radio-frequency sputtered amorphous silicon carbide films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…For the 600°C annealed films, the amount of Si-H and C-H bonds reduces from 61.3% to 9.7% for a-Sio. 5 Co. 5 :H films, but only from 63.4 to 46.1% for a-SiojCo.3:H films. This agrees with the etch results in that the 600 °C annealed a-Si 0 .5C 0 .5:H films showed an drastic decrease in the etch rate, and only a modest reduction for the 600 °C annealed a-Sio.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…For the 600°C annealed films, the amount of Si-H and C-H bonds reduces from 61.3% to 9.7% for a-Sio. 5 Co. 5 :H films, but only from 63.4 to 46.1% for a-SiojCo.3:H films. This agrees with the etch results in that the 600 °C annealed a-Si 0 .5C 0 .5:H films showed an drastic decrease in the etch rate, and only a modest reduction for the 600 °C annealed a-Sio.…”
Section: Methodsmentioning
confidence: 93%
“…The peaks between 740 and 1010 cm" 1 were deconvoluted into the Si-C stretching mode (760-810 cm" 1 ) [5,6], the Si-CH 3 peaks (920-980 cm" 1 ) (980-1010 cm" 1 ) [8]. The peaks between 1580 to 1620 cm" 1 is assigned to the C=C aromatic and olefinic stretching modes [9] and the region between 2000 and 2150 cm" 1 to the stretching mode of the Si-H n bonds [5]. For the 600°C annealed films, the Si-C peak of the a-Si 0 .5C 0 .5:H films increases sharply and the Si-H n , C-H n and Si-CH 3 peaks reduce drastically.…”
Section: Methodsmentioning
confidence: 99%
“…There are comparatively more research in the effect of annealing on a-Si 1-x C x :H films [5][6][7][8] as compare to the oxidation study of this material. We have recently reported oxidation results of a-Si 0.2 C 0.8 :H films [9]. It was found that the oxidation process proceeded very rapidly at a relatively low temperature of 400°C.…”
Section: Introductionmentioning
confidence: 97%
“…Some works had been done on the oxidation of hydrogenated amorphous Si 1−x C x (a-Si 1−x C x :H) films. [10][11][12] Authors demonstrated that the incorporation of the CH 3 radicals introduced void defects and increased the porosity of a-Si 1−x C x :H films, which provided the necessary porous structure for oxide growth. [10,11] The a-Si 1−x C x :H films reported by Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Authors demonstrated that the incorporation of the CH 3 radicals introduced void defects and increased the porosity of a-Si 1−x C x :H films, which provided the necessary porous structure for oxide growth. [10,11] The a-Si 1−x C x :H films reported by Refs. [10,11] with a large number of CH 3 radicals started to oxidize at lower temperature 200 • C and 400 • C in oxygen-containing environments, respectively.…”
Section: Introductionmentioning
confidence: 99%